Induction chemotherapy for locoregionally advanced nasopharyngeal carcinoma - Li, Wen-Fei (Chin J Cancer, 2016)
The value of adding induction chemotherapy (IC) to concurrent chemoradiotherapy (CCRT) for the treatment of locoregionally advanced nasopharyngeal carcinoma (NPC) remains unclear. In our recent article entitled “Induction chemotherapy plus concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in locoregionally advanced nasopharyngeal carcinoma: a phase 3, multicentre, randomised controlled trial” published in the Lancet Oncology, we reported the results of a phase III, multicenter, randomized controlled trial comparing cisplatin, 5-fluorouracil, and docetaxel (TPF) IC plus CCRT versus CCRT alone in patients with T3-4N1/TxN2-3M0 NPC (ClinicalTrials.gov registration number NCT01245959). The IC-plus-CCRT group showed significantly higher 3-year failure-free survival, overall survival, and distant failure-free survival rates than the CCRT-alone group, with an acceptable toxicity profile. Our study suggests that adding TPF IC to CCRT could increase survival rates and reduce distant failure in patients with locoregionally advanced NPC. However, long-term follow-up is required to assess the eventual efficacy and toxicity of this strategy, and a more accurate method to determine prognosis is needed to enable better tailoring of treatment strategy for individual patients.